Empathy and solidarity: communication strategies of Ceará fashion brands in Instagram in times of pandemic - Albuquerque, Ticiana (2020)
From the first time that COVID-19 was mentioned up until the establishment of a nearly global lockdown there was not much time lapsed. A sanitary crisis that immediately impacted the economy, changing the way to conduct businesses and forcing companies to adapt to a new reality that now relied massively on digital platforms to refrain from bankruptcy. The fashion industry took a severe blow with the closing of physical points of sales and a vertiginous drop on the demand for non-essential goods. On the other hand, social media usage increased dramatically with most of the population confined to their homes. Instagram registered peaks of traffic like never before. This article objectifies the analysis through a case study of the communicational strategies applied on Instagram throughout the crisis of three fashion brands from Ceará: Parko, Água de Coco and Catarina Mina. The sample choice was based on the diversity of each brand’s positioning on the market. Laurence Bardin’s (1977) Content Analysis was used as a methodology along with Betina Hollstein’s (2011) work to analyze Instagram’s metrics for the brands statistical data. It was observed that during times of crisis, communication must have a caring trace to it and brands must reply quickly and clearly to its stakeholders. Empathy was the keyword, upstaging commercial strategies. The researched brands changed drastically their editorial storytelling and applied those criteria to their posts, even though, quantitatively, commercial posts were still the main part of the content.